From average Joe to frugal Jane and wasteful John: A quantile regression analysis of Swiss households' electricity use - Ivan Tilov; Benjamin Volland (University of Neuchâtel, Institute of Economic Research (IRENE), 2018)
In this article, we investigate the heterogeneity in household electricity demand in Switzerland. We use a quantile regression approach in order to assess the impacts of electricity prices, income and other socio-demographic characteristics across consumer groups with increasing energy intensities. Estimations show important differences between the "average Joe", the "frugal Jane" and the "wasteful John" for the majority of these variables. Most importantly, households in the lowest deciles of electricity use do not react to changes in electricity prices, while those situated at upper-end of the electricity spectrum exhibit significantly negative short-run price elasticities varying between -0.16, -0.19, -0.21 and -0.27 at the at the 6th, 7th, 8th and 9th deciles, respectively. We also find that low users of electricity react positively and significantly to changes in their wealth compared to intensive electricity consumers. The main policy implications of this work concern the design of price-based measures for reducing electricity consumption in the residential sector and the possibility of accounting for individual responses in tailoring policies, governance mechanisms and business models.
Keywords: Q40; Q41; D12; 330; Heterogeneity; Quantile regression; Households; Electricity; Electricity prices; Switzerland